Належне джерело отримання доказів як критерій їх допустимості - Смирнов, В. А.; Smirnov, V. A. (Юридична наука. - 2019. - № 10 (100). - С. 50-58, 2019)
Встановлено, що для кожного джерела доказів висуваються свої вимоги допустимості, у випадку додержання яких можна говорити про допустимість конкретного доказу в цілому. Запропоновано використовувати такі уніфіковані критерії належного джерела доказів: 1) належний носій інформації; 2) джерело доказів повинно бути визначене КПК України; 3) належне процесуальне оформлення відповідно до процесуальних вимог, що висуваються для кожного джерела доказів; 4) належний порядок приєднання доказів до матеріалів кримінального провадження (для речових доказів).

The article examines scientific approaches to the concept of «appropriate source of evidence». The scientific position that the rule on the proper source of evidence concerns the following aspects is supported: 1) the proper factual source of information about the facts (proper medium of information); 2) the appropriate procedural source (procedural form of consolidation of evidentiary information). Each of the sources of evidence provided by the Criminal Procedure Code has been studied from the standpoint of admissibility requirements. Particular attention is paid to the possibility of using explanations as evidence, given that this practice is becoming increasingly common. Taking into account the positions of the Supreme Court, the status of things and documents voluntarily provided by the participants in the criminal proceedings was determined and a scheme of attaching material evidence to the materials of the criminal proceedings was proposed, which ensures its admissibility. The conditions and criteria of admissibility of the document as a source of evidence are determined. The correlation of documents and material evidence as sources of evidence and some aspects of their delimitation are studied. The criteria of admissibility, which are put forward to the expert’s opinion, are considered. The possibility of using the expert’s opinion as a proper source of evidence has been studied and the coordination of certain provisions of the legislation of Ukraine to ensure its affiliation has been proposed. It is established that for each source of evidence the requirements of admissibility are put forward, in case of observance of which it is possible to speak about admissibility of a concrete proof as a whole. Based on the study, it is proposed to use the following unified criteria for an appropriate source of evidence: 1) an appropriate medium of information; 2) the source of evidence must be determined by the CPC of Ukraine; 3) proper procedural design in accordance with the procedural requirements for each source of evidence; 4) the proper procedure for attaching evidence to the materials of criminal proceedings (for material evidence).

Установлено, что для каждого источника доказательств выдвигаются свои требования допустимости, в случае соблюдения которых можно говорить о допустимости конкретного доказательства в целом. Предложено использовать следующие унифицированные критерии надлежащего источника доказательств: 1) надлежащий носитель информации; 2) источник доказательств должен быть определен УПК Украины; 3) надлежащее процессуальное оформление в соответствии с процессуальными требованиями, предъявляемыми для каждого источника доказательств; 4) надлежащий порядок присоединения доказательств к материалам уголовного производства (для вещественных доказательств).
Appropriate source of obtaining evidence as a criterion of their acceptability
Смирнов, В. А. Належне джерело отримання доказів як критерій їх допустимості / Смирнов В. А. // Юридична наука. - 2019. - № 10 (100). - С. 50-58.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; допустимість доказів; admissibility of evidence; допустимость доказательств; критерії допустимості доказів; criteria for admissibility of evidence; критерии допустимости доказательств; належне джерело доказів; proper source of evidence; надлежащий источник доказательств; забезпечення прав людини; ensuring human rights; обеспечение прав человека